Incorporation of bioleached sulfidic mine tailings in one-part alkali-activated blast furnace slag mortar. (23rd May 2022) - Niu, He; Helser, Jillian; Corfe, Ian J.; Kuva, Jukka; Butcher, Alan R.; Cappuyns, Valérie; Kinnunen, Paivo; Illikainen, Mirja
Highlights: Bioleached sulfidic mine tailings can affect the hydration process. X-ray µCT show mine tailings strongly influence the porosity of final products. Up to 20 wt% mine tailings can be incorporated with high compressive strength (90 MPa). End-of-life leaching test was performed on synergy samples. High immobilization of metal(loid)s including arsenic under acidic conditions. Abstract: Sulfidic mine tailings are potential waste materials from mining and mineral processing, and they can contain a high content of sulfur and metal(loid)s, even after bioleaching. Due to the large amount of tailings waste from historical mining, it is crucial to find alternative methods for utilizing such waste rather than permanent storage in tailings impoundments. One-part alkali-activated slag mortars are promising co-binder systems for the recycling of sulfidic mine tailings thanks to their practicability, easy transportation, and user-friendly production. In this work, up to 50 wt% mine tailings were incorporated into alkali-activated blast furnace slag mortars. C-(N)-A-S-H gels were formed in all final samples with hydrotalcite zeolites. Tailings hardly participate in alkali activation, but they do have a considerable influence on physical and chemical properties. The 20 wt% tailings-containing sample showed the highest compressive strength of 91.1 MPa after 90 days of curing. The results of isothermal calorimetry indicate that incrementally increasing the percentage of tailings promotes the pre-induction reaction but hinders the slag hydration process. In addition, the results of X-ray microcomputed tomography showed higher porosity when the mortar contains more tailings; thus, the sample with 10 wt% mine tailings showed the lowest porosity. According to the European Union batch leaching test, up to 20 wt% bioleached sulfidic mine tailings can be valorized in a co-binder system while remaining below the nonhazardous waste thresholds.